(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
In today’s constructive world, traffic is increasing day by day. It ultimately influenced our road constructions. The objective of this research is to investigate the impact of incorporating low-density polyethylene (LDPE) into bituminous concrete pavements. The construction process of a flexible pavement road involves several stages, including the base course, placement of premix, rolling and check for quality control parameters etc. The robustness of bituminous pavements in resisting moisture damage is significantly impacted by environmental conditions.. Aging & oxidation of bituminous binder lead to the deterioration of the bituminous surfacing due to traffic movement after its construction. Moreover plastic pollution also causes damage to our environment. The process of mixing bituminous materials at elevated temperatures within Hot Mix Plants (HMA) results in the production of dangerous gases. This has a negative effect on the environment by contributing to climate change and reducing the potential transportation distance for flexible pavements. In this article a research investigation was carried out to probe into the influence of substituting Low Density Polyethylene (LDPE) waste in varying proportions within bituminous mixes at five distinct levels of bitumen contents 4.6%, 4.9%, 5.2%, 5.5 and 5.8%. This study investigated how different types of mixes affect Marshall Properties, which are important indicators of the quality and durability of bituminous mixes. The results showed that including plastic in the mixes improved their stability, with the greatest stability achieved when using 6.0% LDPE plastic. Therefore using low density polyethylene is a viable option for creating high quality bituminous mixes.